2020
DOI: 10.21831/jptk.v26i1.24012
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of Technology, Pedagogy and Content Knowledge (TPACK) in Learning

Abstract: The study examined the factors affected teachers' Technology, Pedagogy and Content Knowledge (TPACK). Those factors are Technology Knowledge (TK), Pedagogy Knowledge (PK), Content Knowledge (CK) and Technology Pedagogy Knowledge (TPK). Curriculum 2013 has been applying for 5 years. However, an evaluation of how does the teacher deliver learning subjects (pedagogy knowledge), and the implementation of subject mastery (content knowledge) and technology mastery (technology knowledge) is strongly suggested. The st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 16 publications
1
16
0
2
Order By: Relevance
“…The importance of mastering learning and innovation skills is needed because the students have to keep up-date with technological developments (Absari, Priyanto, & Muslikhin, 2020). TPACK of teachers as the basic framework for learning and innovation skills or 4C (Brown, Neal, & Fine, 2012).…”
Section: The Effect Of Tpack Toward the Learning And Innovation Skill...mentioning
confidence: 99%
See 3 more Smart Citations
“…The importance of mastering learning and innovation skills is needed because the students have to keep up-date with technological developments (Absari, Priyanto, & Muslikhin, 2020). TPACK of teachers as the basic framework for learning and innovation skills or 4C (Brown, Neal, & Fine, 2012).…”
Section: The Effect Of Tpack Toward the Learning And Innovation Skill...mentioning
confidence: 99%
“…Content knowledge refers to the lessons taught by the teacher, pedagogical knowledge refers to how the teacher delivers the material, and technological knowledge refers to the teacher's knowledge of integrating technology in teaching, especially in 21st century education (Sahrir et al, 2021;Voogt, Fisser, Pareja Roblin, Tondeur, & van Braak, 2012). TPACK teachers help and provide teachers' abilities and skills to apply technology in learning process (Absari, Priyanto, & Muslikhin, 2020;Goradia, 2018;Hsu, Liang, Chuang, Chai, & Tsai, 2020). According to Hong, Lin, & Lee (2019), the use of technology, especially information and communication technology (ICT) in education has increased access to education and learning with the assist of technology.…”
Section: The Effect Of Tpack Toward the Learning And Innovation Skill...mentioning
confidence: 99%
See 2 more Smart Citations
“…Most of these studies used non-specific self-assessment instruments (e.g., [21,22]). The significance of individual knowledge domains that can be derived from such studies is inconsistent in that, for example, a direct influence on TPACK can be shown for TK in some studies, but not in others [23][24][25][26].…”
Section: Ict Framework and Models For The Description Of Teacher Digital Competenciesmentioning
confidence: 99%